Ações de saúde mental na atenção primária à saúde: perspectivas para a enfermagem - Stival, Ana Paula Cintra (2019)
Research on the type of intervention with a descriptive-exploratory and qualitative approach, discusses aspects related to the integration process of mental health actions in Primary Health Care (PHC), in view of the need to extend mental health care to the people of community in the territory. With a view to strengthening the Psychosocial Attention Network and mental health care in the field studied, the objective was to identify and analyze the development of mental health actions from the perspective of the supervisors of the family health teams. The following specific objectives were identified: identifying the demands of the field of mental health in the Family Health Strategy (ESF); describe the actions of the mental health field offered by the family health teams; to investigate the factors that influence the development of actions in the field of mental health from the perspective of the supervisors of the Family Health Strategy, in addition to experiencing the implementation of Situational Strategic Planning as a tool for reflection and change in mental health practices in the Family Health Strategy. The research was developed in a medium-sized municipality in the Central West region of Brazil, in which nurses supervising the FHT participated. The data were collected through participant observation at the time of approach and immersion in the field under study, focus groups and by a self-administered questionnaire, aiming at obtaining the professional profile of the participants. Thematic content analysis was followed by qualitative data analysis software. As main results, it was observed that the mental health care in PHC, from a nursing perspective, comprises three dimensions: the reorganization / management of the nursing work process, changes in the professional's posture and effective permanent education plans. In addition, factors that influence the development of actions in the field of mental health by the FHT are described and analyzed. This study indicates the feasibility of instituting permanent education plans for the professionals who are at the forefront of PHC, given the pressing need pointed out by the participants themselves in the discussions undertaken during the research development, as well as highlighting the Situational Strategic Planning as an important strategy for reflection of mental health care actions in the sphere of PHC. Finally, it brings the analysis of these questions into the nursing training dimension.